FENOMENA KOMERSIALISASI TUBUH MANUSIA PERSPEKTIF TEOLOGI TUBUH YOHANES PAULUS II - David Rabim; Raymundus I Made (Diegesis : Jurnal Teologi, 2023)
Commercial bodies spread in the world in order to be able to meet the needs. The body is no longer seen as the most expensive part but can be traded. Sexual harassment is also an act of humiliation against the body that needs to be corrected. This study aims to understand the body from the perspective of John Paul II. The research method used is descriptive qualitative, with the data source through library research. The research results show that John Paul II understood the human body as a representation of God. The invisible God is invisibly present in the body. The human body becomes an inseparable part of Him. The body also speaks of the whole person's noble dignity and worth. Faced with that body, man can do nothing but respect it. Respect for the body is a must. It means the phenomenon of humanity which places the body as a commodity object from itself against God's intention and purpose in creating human beings. Humans are called not to objectify others but to build true brotherhood.